Indian silver punch-marked coins in ancient Ceylon – a case study: The Tissamahārāma hoards - Walburg, Reinhold (Zeitschrift für Archäologie Außereuropäischer Kulturen, 2023)
The article deals with two small hoards of punch-marked coins unearthed during the course of archaeological excavations in Tissamahārāma, the capital city of the ancient dominion of Rohana, Śrī Lankā. The comparison of the coins from the two complexes which belong to the second and third century AD respectively provides insights into the local monetary history of this city. The discovery of these hoards offered the opportunity to look beyond the local coin circulation and to examine the role these coins played in the economic history of Śrī Lankā in general; this in turn necessitated a compilation and discussion of all known punch marked coins hitherto unearthed on the island.